Okulistyczna sala operacyjna – możliwości ograniczenia zanieczyszczeń i zakażeń. Cz. I. Dekontaminacja bioaerozolu powietrza - Kałużny, Józef; Muszyński, Zygmunt; Kałużny, Bartłomiej (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Even the best technical and organizational methods will not prevent the infection of the spot being operated on. The risks may be caused for example by the microbial air pollution of the operating theatre. Ways of air decontamination for the purposes of air conditioning and ventilating used in the operating theatre are both up-to-date and essential. Decontamination methods involve filtration by means of HEPA, ULPA, EU-13 filters with 99.99% effectiveness for ≤ 0.1 μm particles. The most suitable sterile air flow is a displacing, vertical, ceiling system e.g. 3.2 x 3.2 m according with the requirements of the laminar air flow (LAF) at the speed of 0.3-0.5 m/sec. The above system should provide 1 cfu/m3 over the operating theatre and „safe bio conditions” at 30-100 cfu/m3 during at least 3-hour work. Decontamination by means of filtration is cost effective both in production and in use: the cost of filters exchanging, humidification, the problem of Legionella pneumofila or the air cooling system. MFI (Multifunction Ion Air Cleaning) does not show the abovementioned limitations. The method makes use of the combination of the ionising processes and electrostatic attraction of particles > 0.003 um which include cells of bacteria, fungi and some viruses. MFI technology used in Nanobio E 310 (Genano) working at 250 m3 /h allows for eliminating microorganisms from the air at ≤ 1cfu/m3. These decontamination methods make it possible to achieve appropriate microbiological standards when the appliance is properly used.